A review of global automotive industry's competitive strategies. Issue 4 (7th October 2019) - Mohammad Nazir, Norzuliana; Shavarebi, Kamran
Abstract : Purpose: The purpose of this paper is to study the latest global automotive industry's competitive strategies comprehensively before being categorized into countries, automakers and other scholars. Design/methodology/approach: In total, 54 most relevant articles have been chosen from various journals and databases between the years 2017 and 2018 with search items "Competitive" and "Automotive" for the most updated review. Based on findings, there are total 133 competitive strategies. Findings: Based on the review and analysis of the literature, all of these three categories, countries, automakers and other scholars, are using new product development (NPD) as a competitive strategy. As a result, further research on NPD, specifically in the automotive industry area, is vital for industry's competitiveness based on this study. Research limitations/implications: Firms are advised to be ahead from the competitors in terms of business model or in their management in order to attain sustainability. However, to the authors' best knowledge, there is no comprehensive review on competitive strategies for automotive globally by countries, automakers and other scholars. Practical implications: The competitive strategies are reviewed comprehensively so that other than guiding the further research, they can help automakers, especially from developing countries, to improve the strategies suitable to the current trend. Social implications: Automotive industry plays a key role in the day-to-day activity of human life by not only providing mobility but also having an enormous impact of the industry on economic, environmental and social activities throughout the globe. Originality/value: Most of the articles reviewed related to certain country or comparison between the countries, and certain automaker or comparison between the automakers, but still no study about comprehensive review globally covered in the larger scope, divided into three categories; countries, automakers and other scholars even though the study is vital not only to academicians but also to practitioners.